THE LEGAL CONCEPT OF PERSONA AND THE PROTECTED STATUSES. CONSUMERS AND ADHERENTS CASE IN ARGENTINE ECONOMIC LAW - Lell, Helga María (2019)
This article departs from the legal concept of person as a being that plays different roles in the legal scene. This idea comes from a metaphor that remembers the antique masks on the Latin and Greek theatres. In Argentinian legal system, the concept of person cannot be understood without the characteristics of dignity, autonomous and being inviolable. In this context, in nowadays paradigm, person is understood specially from different roles in order to protect in the best possible way concreting rights. That leads to the fact that in economic right some individuals get special attention and special regulations in order to be more equal to the strongest part in the relationship. According to this, this paper will focus on the consumers/users and adherent’s roles. Legal protection is expressed through interpretative statements that change contractual law as it is usually conceived. It takes for granted that both parts in a contract are not equals but also treats differently those parts. The aim of the article is to show how the return of statuses has become a protective legal tool in the case of economic law in Argentinian legal system in consumer’s relationships.